Glyco-copolypeptide grafted magnetic nanoparticles: the interplay between particle dispersion and RNA loading. Issue 19 (26th April 2016) - Borase, T.; Fox, E. K.; Haddassi, Fadwa El; Cryan, S.-A.; Brougham, D. F.; Heise, A.
Abstract : Lysine-glyco-copolypeptide grafted superparamagnetic iron oxide nanoparticles were prepared through N -carboxyanhydride (NCA) copolymerization. Statistical and block copolymer arrangements were obtained while keeping the overal composition constant. Abstract : Lysine-glyco-copolypeptide grafted superparamagnetic iron oxide nanoparticles were prepared through N -carboxyanhydride (NCA) copolymerization. Statistical and block copolymer arrangements were obtained while keeping the overall composition constant. Both type of nanoparticles are fully water dispersible, which is key for T 1 -weighted magnetic resonance imaging (MRI) applications. A synergistic effect between siRNA loading and imaging properties was observed in the statistical copolymer arrangement allowed a significantly higher loading while retaining full particle dispersion, as required for T 1 -weighting.